Nutrition Science and Everyday Application - Callahan, Alice; Leonard, Heather; Powell, Tamberly (Open textbook library., 2024)
This book is designed as an Open Education Resource (OER) for introductory nutrition courses and has been adopted for use in high schools and colleges. Topics covered include basic nutrition and metabolism, information literacy, body weight and health, nutrition across life stages, dietary supplements, an in-depth look at each of the macronutrients, and major functions of vitamins and minerals. The second edition of Nutrition: Science and Everyday Application was released in August 2022. The second edition includes a fully revised Unit 7 (Body Weight and Health) and minor revisions to Unit 10 (Nutrition and Physical Activity). In June 2023, Unit 2 (Nutrition Science and Information Literacy) was significantly updated along with the ancillary materials for Unit 2. The remainder of the OER and the accompanying ancillary materials are the same as the first edition, originally published in